2004
DOI: 10.1111/j.0009-9163.2004.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

New insights in congenital bowing of the femora

Abstract: The aim of this study is to review the clinical, radiological and molecular findings of the bent bone dysplasia group including Stüve-Wiedemann syndrome due to LIFR mutations, Compomelic dysplasia due to SOX9 mutations and Kyphomelic dysplasia with no known molecular bases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…In the Revised International Nosology and Classification of Genetic Disorders of Bone—200612, SWS has been classified under the bent skeletal dysplasias along with campomelic dysplasia (CMPD), Cumming syndrome and kyphomelic dysplasia17. Alternative diagnostic considerations in the setting of bowed femora and mild‐to‐moderate micromelia would be Antley–Bixler syndrome, femoral hypoplasia‐unusual facies syndrome (FH‐UFS), osteogenesis imperfecta (OI) and diastrophic dysplasia18–21.…”
Section: Discussionmentioning
confidence: 99%
“…In the Revised International Nosology and Classification of Genetic Disorders of Bone—200612, SWS has been classified under the bent skeletal dysplasias along with campomelic dysplasia (CMPD), Cumming syndrome and kyphomelic dysplasia17. Alternative diagnostic considerations in the setting of bowed femora and mild‐to‐moderate micromelia would be Antley–Bixler syndrome, femoral hypoplasia‐unusual facies syndrome (FH‐UFS), osteogenesis imperfecta (OI) and diastrophic dysplasia18–21.…”
Section: Discussionmentioning
confidence: 99%
“…This is an autosomal recessive syndrome comprising of long bone bowing, scoliosis, and respiratory compromise (Cormier-Daire et al 2004 ; Hassan et al 2010 ). Although usually lethal in infancy, some children survive.…”
Section: Stüve-wiedemann Syndromementioning
confidence: 99%
“…Congenital bowing of the long bones is a hallmark feature of STWS [1], but it is not unique to STWS and manifests in other syndromes including type IX Ehlers-Danlos syndrome, Campomelic Displasia, Larsen syndrome and other conditions. [109-112]. Some have suggested that prenatal bowing of the long bones results from the mechanical forces of imbalanced muscles acting on structurally weak bones in utero [113-115].…”
Section: A Note About Bowing Of the Long Bonesmentioning
confidence: 99%